The utility of the reperfusion rate of tissue oxygen saturation as a measure of vascular endothelial function in adolescents: reliability, validity and sensitivity - Kranen, Sascha H.; Oliveira, Ricardo S.; Bond, Bert; Williams, Craig A.; Barker, Alan R. (Frontiers in Physiology, 2023)
Introduction: The near-infrared spectroscopy (NIRS)-derived reperfusion rate of tissue oxygen saturation (slope 2 StO2) may provide a surrogate measure of vascular function, however, this has yet to be examined in a paediatric population. This study investigated in adolescents: 1) the between-day reliability of NIRS-derived measurements; 2) the relationship between slope 2 StO2 and macro- (flow-mediated dilation, FMD) and microvascular (peak reactive hyperaemia, PRH) function; and 3) the effect of high-intensity interval exercise (HIIE) on slope 2 StO2, FMD, and PRH. Methods: Nineteen boys (13.3 ± 0.5 y) visited the laboratory on two occasions, separated by ∼ 1 week. On visit 1, participants underwent simultaneous assessment of brachial artery FMD and slope 2 StO2 and PRH on the internal face of the forearm. On visit 2, participants completed a bout of HIIE with slope 2 StO2, FMD and PRH measured pre-, immediately post- and 1.5 h post-exercise. Results: Slope 2 StO2 showed no mean bias (p = 0.18) and an intraclass correlation coefficient of 0.67 (p = 0.003) between visits. No significant correlation between slope 2 StO2 and FMD or PRH was observed on visit 1 (r = −0.04, p = 0.89 and r = −0.30, p = 0.23, respectively) or visit 2 pre-exercise (r = −0.28, p = 0.25 and r = −0.31, p = 0.20, respectively). Compared to pre-exercise, FMD decreased immediately post-exercise (p < 0.001) and then increased 1.5 h post-exercise (p < 0.001). No significant change was detected for slope 2 StO2 (p = 0.30) or PRH (p = 0.55) following HIIE. Conclusion: In adolescents, slope 2 StO2 can be measured reliably, however, it is not correlated with FMD or PRH and does not follow the acute time course of changes in FMD post-exercise. Hence, the use of slope 2 StO2 as a surrogate measure of vascular function in youth must be refuted.